How the light gets in : [large type] a novel - Maynard, Joyce, 1953- (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
After her husband's death, Eleanor returns to her New Hampshire farm to care for their brain-injured son while facing family tensions, personal struggles and national events, in the follow-up to Count the Ways.